Harnessing YouTube in advancing biodiversity conservation efforts and awareness across Africa - Basooma,Anthony; Nakiyende,Herbert; Natugonza,Vianny; Basooma,Rose (PeerJ, 2025)
YouTube (YT), an online video content application, has revolutionized the dissemination of information in various fields, including medicine, entertainment, and conservation science. Its potential in disseminating biodiversity conservation information has not been well assessed, especially in Africa, a biodiversity hotspot. When such assessments are conducted, they are usually species-specific, activity-based, or localized, making broader generalizations difficult. We evaluated the viewership and interaction of the videos posted about Africa across different organism groups, countries (geopolitical units), geographical regions, ecoregions, and channels (content creators). We assessed 431 videos, which collectively garnered 32,630,126 views, 364,700 likes, and 48,839 comments across 274 channels, five regions, and 31 African countries. The mean daily views varied significantly across countries, regions organism groups, and channels. Notably, more views per day were from biodiversity-rich countries, such as Madagascar, and most videos were posted from South Africa. Government and academic institutions posted fewer videos than individually owned and international biodiversity-related non-governmental organization (NGO) channels. Also, most channels posting about African biodiversity are based in the United States of America. Increased attention to biodiversity through social media engagement will likely stimulate external funding, international collaborations, policymaking, and participatory programs, benefiting both the public and organizations such as NGOs and governments. We observed a great need for increased participation by African-based content creators, primarily by government institutions, to effectively adopt a strong social media strategy to communicate information about biodiversity conservation, especially to the growing online population.
Keywords: Climate change; Invasive species; Species extinction; Social media platforms; Topical analysis